Smart multiplication media on mathematical problem-solving skills among in Madrasah Ibtidaiyah - Amandha Fhadillah Siregar; Nurdiana Siregar (Universitas Pendidikan Indonesia, 2025)
Mathematics learning in early-grade students still faces challenges, particularly in the area of problem-solving skills, which remain relatively low. This study aims to examine the effect of using a smart multiplication board on the mathematical problem-solving abilities of early-grade students at MIN Pematangsiantar. A quantitative approach with a quasi-experimental design, specifically the pre-test and post-test control group design, was employed. The study sample consisted of 20 third-grade students, divided into two groups: an experimental class using the smart multiplication board and a control class that applied conventional teaching methods. The research instrument was a set of mathematical word problems. The findings revealed a significant difference between the performance of students in the experimental and control groups. The t-test value indicates a large effect size. This result demonstrates that the smart multiplication board significantly enhances students’ mathematical problem-solving skills. Its effectiveness lies in its concrete, visual, and interactive nature, which supports logical and systematic thinking in line with children’s cognitive development and Polya’s problem-solving stages. Abstrak Pembelajaran Matematika pada peserta didik kelas awal masih menghadapi tantangan terutama dalam kemampuan pemecahan masalah yang tergolong rendah. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media papan pintar perkalian terhadap kemampuan pemecahan masalah Matematika peserta didik kelas awal di MIN Pematangsiantar. Metode yang digunakan adalah pendekatan kuantitatif dengan desain quasi eksperimen berbentuk pre-test and post-test control group design. Sampel penelitian 20 peserta didik kelas 3 terdiri dari dua kelas yaitu kelas eksperimen yang menggunakan media papan pintar dan kelas kontrol yang menggunakan metode pembelajaran konvensional. Instrumen penelitian berupa soal cerita Matematika. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan antara hasil belajar peserta didik di kelas eksperimen dan kelas kontrol. Nilai signifikansi hasil uji t Test pada kategori tinggi menunjukkan bahwa penggunaan media papan pintar berpengaruh secara signifikan terhadap peningkatan kemampuan pemecahan masalah Matematika. Media ini terbukti efektif karena bersifat konkret, visual, dan interaktif, serta mendukung proses berpikir logis dan sistematis sesuai tahap perkembangan kognitif anak dan tahapan pemecahan masalah menurut teori Polya. Kata Kunci: Madrasah Ibtidaiyah; Matematika; papan pintar; pemecahan masalah